(untitled) (Medico Legal Update, 2020)
The study to assess Knowledge on maternal and child health services among women in reproductive age group in Mahabalipuram, Kanchipuram District, Tamil Nadu, India” The objectives were to assess the knowledge of women regarding maternal and child health services and associate the level of knowledge with selected demographic variables among women in reproductive age group. 184 samples were selected by convenient sampling technique. Data collected by structured questionnaire. The collected data was tabulated and analysed. Descriptive and inferential statistical were used. The results are majority 60% of women had moderate knowledge where as minority 12% had inadequate knowledge. Demographic variables like Age ?2=12.14, Educational status ?2=16.572, Monthly income ?2=16.4828, Type of family ?2=23.788(p?0.05) were significant where as Marital status ?2=1.0432, Occupational status ?2=0.7601, Number of pregnancy ?2=0.8079 (p?0.05) not significant with the selected demographic variables among women in reproductive age group